Virtual Communication among Mobile Legends: Bang Bang Players through the In-Game Chat Feature among Adolescents in Telanaipura, Jambi City - Muhammad Azizul Hakim; Qatrun Nada (Journal of Communication, 2026)
The rapid growth of team-based online games such as Mobile Legends: Bang Bang (MLBB), which serve not only as entertainment but also as a space for virtual social interaction. This game, which requires coordination among five players on a single team, presents complex communication dynamics through its chat feature, yet it often faces technical obstacles as well as toxic communication. The purpose of this study is to examine the communication patterns of MLBB players in the chat column, specifically the forms of communicative interaction and the obstacles that arise during gameplay. This study employs the All-Channel Communication Pattern Theory, which views communication as an open process without hierarchical boundaries among team members. The methodology used is a descriptive qualitative approach, with data collection techniques including in-depth interviews, non-participant observation, and documentation. Informants were selected via purposive sampling, comprising 12 active MLBB players in the Telanaipura area of Jambi City. The research findings indicate that the communication patterns that emerge are dynamic and open, reflecting the characteristics of an All-Channel model with three forms of communication: dyadic (two-way) in the early phase of the game, triadic (three-way) in the middle phase, and global network (multi-directional) in the final phase. Communication barriers identified include technical constraints such as network instability (lag) and non-technical barriers such as toxic communication, including flaming, blaming, and sarcasm, which negatively impact focus, motivation, and team performance. This study underscores that effective and ethical communication is essential for fostering teamwork and creating a more positive gaming environment.